Exogenous shocks and time-varying price persistence in the EU27 - Guglielmo Maria Caporale; Luis A. Gil-Ala\~na; Amir Imeri (Journal of Applied Economics, 2024)
This paper analyses monthly price persistence in the EU27 countries over the period 2010-2022 using a fractional integration framework, where the measure of persistence is the fractional differencing parameter d. In addition to full sample estimates, subsample and recursive ones are obtained to examine time variation. On the whole, the results provide clear evidence that both the exogenous shocks considered (namely, the COVID-19 pandemic and the Russia-Ukraine war) have generally increased price persistence in the EU27 (despite their heterogeneity), although the recursive estimates suggest that their impact might have peaked and might now be decreasing. Therefore, any policies adopted to counteract those shocks should be gradually phased out. The exceptions are the Southern European countries, where price persistence appears to have decreased, though in Italy the recursive analysis indicates that it is now rising sharply.
Keywords: 330; COVID-19 pandemic; fractional integration; Price persistence; Russia-Ukraine war